Case report: Early-onset osteoporosis in a patient carrying a novel heterozygous variant of the WNT1 gene - Campopiano, Maria Cristina; Fogli, Antonella; Michelucci, Angela; Mazoni, Laura; Longo, Antonella; Borsari, Simona; Pardi, Elena; Benelli, Elena; Sardella, Chiara; Pierotti, Laura; Dinoi, Elisa; Marcocci, Claudio; et al. (Frontiers in Endocrinology, 2022)
WNT1 gene is crucial in bone development and homeostasis. Homozygous mutations in WNT1 cause severe bone fragility known as osteogenesis imperfecta type XV. Moreover, heterozygous WNT1 mutations have been found in adults with early-onset osteoporosis. We identified a 35-year-old Caucasian woman who experienced multiple vertebral fractures two months after the second pregnancy. There was no history of risk factors for secondary osteoporosis or family history of osteoporosis. Dual-energy X-ray absorptiometry confirmed a marked reduction of bone mineral density (BMD) at the lumbar spine (0.734 g/cm2, Z-score -2.8), femoral neck (0.48 g/cm2, Z-score -3.5), and total hip (0.589 g/cm2, Z-score -3.0). Blood tests excluded secondary causes of bone fragility. Genetic analysis revealed a heterozygous missense mutation (p.Leu370Val) in the WNT1 gene. Varsome classified it as a variant of uncertain significance. However, the fact that the Leucine residue at position 370 is highly conserved among vertebrate species and the variant has a very low allelic frequency in the general population would exclude the possibility of a polymorphism. The patient was treated for two years with teriparatide therapy associated with calcium and vitamin D supplements. During the follow-up period she did not report further clinical fractures. After 24 months of teriparatide, BMD increased at lumbar spine (+14.6%), femoral neck (+8.3%) and total hip (+4.9%) compared to baseline. We confirm that the heterozygous WNT1 mutation could cause a variable bone fragility and low turnover osteoporosis. We suggest that teriparatide might be the most appropriate available therapy for this case.